Aboriginal autonomy and development in northern Quebec and Labrador - Scott, Colin (CEL - Canadian Publishers Collection., 2001)
On autonomy and development / Colin H. Scott -- Healing the past, meeting the future / Peter Penashue -- Shaping modern Inuit territorial perception and identity in the Quebec-Labrador peninsula / Ludger Muller-Wille -- Writing legal histories on Nunavik / Susan G. Drummond -- The landscape of Nunavik/the territory of Nouveau-Quebec / Peter Jacobs -- Aboriginal rights and interests in Canadian northern seas / Monica E. Mulrennan and Colin H. Scott -- Territories, identity, and modernity among the Atikamekw (Haut St-Maurice, Quebec) / Sylvie Poirier -- Voices from a disappearing forest : government, corporate, and Cree participatory forestry management practices / Harvey A. Feit and Robert Beaulieu -- Conflicts between Cree hunting and sport hunting : co-management decision making at James Bay / Colin H. Scott and Jeremy Webber -- Becoming a mercury dealer : moral implications and the construction of objective knowledge for the James Bay Cree / Richard T. Scott -- Media contestation of the James Bay and Northern Quebec Agreement : the social construction of the "Cree problem" / Donna Patrick and Peter Armitage -- Low-level military flight training in Quebec-Labrador : the anatomy of a northern development conflict / Mary Barker -- The land claims negotiations of the Montagnais, or Innu, of the province of Quebec and the management of natural resources / Paul Charest -- Community dispersal and organization : the case of Ouje-Bougoumou / Abel Bosum -- Gathering knowledge : reflections on the anthropology of identity, aboriginality, and the annual gatherings in Whapmagoostui, Quebec / Naomi Adelson -- Building a community in the town of Chisasibi / Susan Jacobs -- Cultural change in Mistissini : implications for self-determination and cultural survival / Catherine James -- The decolonization of the self and the recolonization of knowledge : the politics of Nunavik health care / Josee G. Lavoie -- Country space as a healing place : community healing at Sheshatshiu / Cathrine Degnen -- The concept of community and the challenge for self-government / Hedda Schuurman -- The double bind of aboriginal self-government / Adrian Tanner -- Ways forward / Colin H. Scott